Seagrass Meadow Condition Assessment: A Case Study of Seagrass Meadows in Pulau Banyak District, Aceh Singkil - Lisdayanti, Eka; Najmi, Nurul; Muktaridha, Muktaridha (Jurnal Biologi Tropis, 2024)
Seagrass beds are one of the coastal ecosystems that have an important role in maintaining the balance of the marine environment. Indonesia is known for its rich seagrass species but not much has been reported, especially in Aceh waters.This study aims to identify and analyse the distribution and condition of seagrass health through the percentage cover and dominance of seagrass species in Pulau Banyak District, Aceh Singkil Regency. Seagrass research was conducted in July 2024 at 3 different stations, namely Nago, Matahari and Panjang Islands. The research method used was the method of drawing a 100 m long line transect, with each station being repeated 3 times at 50 m, so that the seagrass area observed was 100 m2. Differences in the condition of the aquatic environment showed differences in the presence of seagrass species found. A total of 4 seagrass species were recorded in this study, namely Thalassia hemprichii, Enhalus acoroides, Cymodocea rotundata and Halophila ovalis. There is a difference in the number of seagrass species found in the 2015 and 2023 time periods, the 2024 survey recorded 4 species from the previous 5 seagrass species. The highest percentage of seagrass cover was found on Nago, Matahari and Panjang Islands with percentages of 19.98%, 3.69% and 1.23% respectively. The highest overall seagrass species cover was T. hemprichii at 60.268%, while the lowest seagrass species was H. ovalis at 3.534%. Based on the results of the analysis of the percentage of seagrass cover of the entire research station, it is concluded that seagrass in the waters of Pulau Banyak is included in the category of sparse cover, with poor condition status (≤29.9).